Measuring The quality of services provided to Customers in Jeddah Municipality - Fadhel, Fatima Abdulraqeb; Al-Sharief, Raja Yahya (Journal of Economic, Administrative and Legal Sciences, 2020)
The study aimed to measuring the quality of the services provided by the secretariat of Jeddah’s Governate using the gap between perceptions and expectations (SERVQUAL). The descriptive (analytical) approach was used, to achieve the objectives of the study; data were collected using a questionnaire consisting of five main dimensions (concrete, reliability, response, assurance, empathy), the community of the study consists of the reviewers of the Secretariat of Jeddah, where the study was applied to a randomly selected sample, and questionnaires were distributed to them with a total of (325) questionnaires valid for analysis. The results of the study showed that there is a gap in the quality of services provided by the Secretariat of Jeddah, since the actual quality of service is below the expected quality level. There are also statistically significant differences between opinions of the sample members on the quality of services expected and actual in each dimension (reliability, response, assurance, empathy), as well as the overall degree of quality of services expected and actual according to gender variable. In the light of the findings, the study reached recommendations based on the (SERVQUAL) scale; the most important of them was the promotion of the focusing culture on reviewers through the attention of the complaints, the identification of their desires and determine them periodically through the process of continuous evaluation; to ensure improvement of the quality of municipal services.